Therapy in the Course of Kidney Graft Rejection—Implications for the Cardiovascular System—A Systematic Review - Jakub Mizera; Justyna Pilch; Ugo Giordano; Magdalena Krajewska; Mirosław Banasik (Life, 2023)
Kidney graft failure is not a homogenous disease and the Banff classification distinguishes several types of graft rejection. The maintenance of a transplant and the treatment of its failure require specific medications and differ due to the underlying molecular mechanism. As a consequence, patients suffering from different rejection types will experience distinct side-effects upon therapy. The review is focused on comparing treatment regimens as well as presenting the latest insights into innovative therapeutic approaches in patients with an ongoing active ABMR, chronic active ABMR, chronic ABMR, acute TCMR, chronic active TCMR, borderline and mixed rejection. Furthermore, the profile of cardiovascular adverse effects in relation to the applied therapy was subjected to scrutiny. Lastly, a detailed assessment and comparison of different approaches were conducted in order to identify those that are the most and least detrimental for patients suffering from kidney graft failure.